Targeting the Annexin A1-FPR2/ALX pathway for host-directed therapy in dengue disease - Vivian Vasconcelos Costa; Michelle A Sugimoto; Josy Hubner; Caio S Bonilha; Celso Martins Queiroz-Junior; Marcela Helena Gonçalves-Pereira; Jianmin Chen; Thomas Gobbetti; Gisele Olinto Libanio Rodrigues; Jordana L Bambirra; Ingredy B Passos; Carla Elizabeth Machado Lopes; et al. (eLife, 2022)
Host immune responses contribute to dengue’s pathogenesis and severity, yet the possibility that failure in endogenous inflammation resolution pathways could characterise the disease has not been contemplated. The pro-resolving protein Annexin A1 (AnxA1) is known to counterbalance overexuberant inflammation and mast cell (MC) activation. We hypothesised that inadequate AnxA1 engagement underlies the cytokine storm and vascular pathologies associated with dengue disease. Levels of AnxA1 were examined in the plasma of dengue patients and infected mice. Immunocompetent, interferon (alpha and beta) receptor one knockout (KO), AnxA1 KO, and formyl peptide receptor 2 (FPR2) KO mice were infected with dengue virus (DENV) and treated with the AnxA1 mimetic peptide Ac2-26 for analysis. In addition, the effect of Ac2-26 on DENV-induced MC degranulation was assessed in vitro and in vivo. We observed that circulating levels of AnxA1 were reduced in dengue patients and DENV-infected mice. Whilst the absence of AnxA1 or its receptor FPR2 aggravated illness in infected mice, treatment with AnxA1 agonistic peptide attenuated disease manifestationsatteanuated the symptoms of the disease. Both clinical outcomes were attributed to modulation of DENV-mediated viral load-independent MC degranulation. We have thereby identified that altered levels of the pro-resolving mediator AnxA1 are of pathological relevance in DENV infection, suggesting FPR2/ALX agonists as a therapeutic target for dengue disease.